Britain's moment in Palestine - Cohen, Michael Joseph, 1940-, author.
1 online resource (xvi, 518 pages)
Keywords: "Analysing why, and how, the British took on the Palestine Mandate; this book explores how their interests and policies changed during its course, and why they left. Issuing the Balfour Declaration in 1917 for military and strategic reasons, the first decade of the Mandate saw an influx of Jewish capital mobilized by the Zionists which enabled the British to fund not only the administration of Palestine, but also her imperial projects there. In the mid-1930s, as the clouds of World War Two gathered, Britain's commitment to Zionism was superseded by the need to secure her strategic assets in the Middle East and consequently her policy turned to favour the Arabs. The post war period saw Britain abandon any attempts to impose a settlement in Palestine that would be acceptable to the Arab States and the government referred Palestine to the United Nations, without recommendations, leaving the antagonists to settle their conflict on the battlefield. Based on archival sources and the most up-to-date scholarly research, this comprehensive history is a must-read for anyone with an interest in Israel, and the Middle East in general"-- "This book provides a comprehensive analysis of British policies in Palestine during the 28 years for which it held the League of Nations Mandate. It examines how and why they conquered Palestine, their relations with Arabs and Jews and why they left in a hurry in 1948"--